Period Change of V1162 Orionis Variable Star - รัตนมาลา, รณกฤต; ศิลปวิลาวัณย์, วันธนา (KKU Science Journal, 2013)
The study of period change of variable star V1162 Orionis was conducted at Princess Sirindhorn Observatory, Chiang Mai University. The observation was done via CCD photometer in blue (B) and visible (V) bands. The data were employed to analyze and plot light curves. The period change analysis by O-C diagram was shown the decreasing rate at 11.2886x10-12 day/cycle (4.527 msec/year). The result likely showed that the V1162 Orionis was collapsed.